2015
DOI: 10.12965/jer.150189
|View full text |Cite
|
Sign up to set email alerts
|

The effects of band exercise using proprioceptive neuromuscular facilitation on muscular strength in lower extremity

Abstract: The purpose of this study was to examine whether a six-week elastic band exercise program using proprioceptive neuromuscular facilitation (PNF) can increase isotonic strength of abductor muscles in the lower extremity. Twenty-eight healthy students from S university were divided into an experimental group and control group. Each group was participated in pre and post-measurement in isotonic strength using an isotonic analyzer, En-treeM. Experimental group performed elastic band exercise using PNF pattern for a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 7 publications
2
17
1
Order By: Relevance
“…Three weekly sessions were conducted in five of the studies. The study protocols ranged from 2 to 9 sets, while 3 sets was the most widely used pattern (Behm, 1991;Rhyu, Kim & Park, 2015;Thorborg et al, 2016). Most trials used 10 repetitions, while one study performed repetitions to maximal muscle fatigue (Hostler et al, 2001).…”
Section: Characteristics Of the Studies In Young Adultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three weekly sessions were conducted in five of the studies. The study protocols ranged from 2 to 9 sets, while 3 sets was the most widely used pattern (Behm, 1991;Rhyu, Kim & Park, 2015;Thorborg et al, 2016). Most trials used 10 repetitions, while one study performed repetitions to maximal muscle fatigue (Hostler et al, 2001).…”
Section: Characteristics Of the Studies In Young Adultsmentioning
confidence: 99%
“…Thorborg et al (2016) observed an improvement in isometric hip flexion strength after 6 weeks of elastic resistance training. Some researchers have combined elastic resistance with proprioceptive neuromuscular facilitation (PNF) techniques, reporting improvements in joint mobility, reporting benefits in the development of the strength, and the balance through of improving the responsiveness of the skeletal-muscle system (Jonghwan, Chulhyun, Kyumoon, Hyeonju & Byeungok, 2003;Rhyu, Kim & Park, 2015). Only Hostler et al (2001) analyzed the effect of elastic resistance exercise on some physiological biomarkers of health, finding no significant improvements.…”
Section: Effects Of Training With Elastic Bands In Young Adultsmentioning
confidence: 99%
“…26 Resistance band exercises are helpful in healthy and frail older adults. 27,28 Such exercises have been found to enhance muscle strength and endurance; 29,30 improve balance, agility, and gait speed; 29,31,32 promote muscle hypertrophy; 33 and boost lower extremity function. 34 Furthermore, resistance band exercises have been reported to improve functional ability, 29 increase cardiovascular endurance, 29,31 increase flexibility and range of joint motion, 29,35 and enhance overall physical fitness of older adults.…”
mentioning
confidence: 99%
“…For the RP increase in the Fz derivation, especially in G2, it is assumed that this area of the cortex remained more active, since the participant already had a knowledge of the task that would be performed later, since it was previously trained, besides the Diagonal motion requires more attention because it is a movement that activates the CNS generally speaking ( RosĂĄrio, 2011 ), acting on the three motion planes (frontal, sagittal, and transverse), and consequently promoting a greater neuromuscular recruitment ( Pereira and Gonçalves, 2012 ; Rhyu et al, 2015 ). For this result one can also consider the fact that this derivation is located in a region of interconnection of the brain lateral areas, presumably assuming an increase in power concentration.…”
Section: Discussionmentioning
confidence: 99%